Exfoliated black phosphorous-mediated CuAAC chemistry for organic and macromolecular synthesis under white LED and near-IR irradiation - Kocaarslan, Azra; Eroglu, Zafer; Metin, Önder; Yagci, Yusuf (Beilstein Journal of Organic Chemistry, 2021)
The development of long-wavelength photoinduced copper-catalyzed azide–alkyne click (CuAAC) reaction routes is attractive for organic and polymer chemistry. In this study, we present a novel synthetic methodology for the photoinduced CuAAC reaction utilizing exfoliated two-dimensional (2D) few-layer black phosphorus nanosheets (BPNs) as photocatalysts under white LED and near-IR (NIR) light irradiation. Upon irradiation, BPNs generated excited electrons and holes on its conduction (CB) and valence band (VB), respectively. The excited electrons thus formed were then transferred to the CuII ions to produce active CuI catalysts. The ability of BPNs to initiate the CuAAC reaction was investigated by studying the reaction between various low molar mass alkyne and azide derivatives under both white LED and NIR light irradiation. Due to its deeper penetration of NIR light, the possibility of synthesizing different macromolecular structures such as functional polymers, cross-linked networks and block copolymer has also been demonstrated. The structural and molecular properties of the intermediates and final products were evaluated by spectral and chromatographic analyses.
Keywords: black phosphorus; click chemistry; heterogeneous photocatalyst; near infrared; phosphorene

(untitled) - Kolb, H. C.; Finn, M. G.; Sharpless, K. B. (Angew. Chem., Int. Ed., 2001)

(untitled) - Rostovtsev, V. V.; Green, L. G.; Fokin, V. V.; Sharpless, K. B. (Angew. Chem., 2002)

(untitled) - Tornøe, C. W.; Christensen, C.; Meldal, M. (J. Org. Chem., 2002)

(untitled) - Lutz, J.-F.; Börner, H. G. (Prog. Polym. Sci., 2008)

(untitled) - Kolb, H. C.; Sharpless, K. B. (Drug Discovery Today, 2003)

(untitled) - Lutz, J.-F. (Angew. Chem., Int. Ed., 2007)

(untitled) - Xi, W.; Scott, T. F.; Kloxin, C. J.; Bowman, C. N. (Adv. Funct. Mater., 2014)

(untitled) - Johnson, J. A.; Finn, M. G.; Koberstein, J. T.; Turro, N. J. (Macromol. Rapid Commun., 2008)

(untitled) - Kempe, K.; Krieg, A.; Becer, C. R.; Schubert, U. S. (Chem. Soc. Rev., 2012)

(untitled) - Moses, J. E.; Moorhouse, A. D. (Chem. Soc. Rev., 2007)

(untitled) - Adzima, B. J.; Tao, Y.; Kloxin, C. J.; DeForest, C. A.; Anseth, K. S.; Bowman, C. N. (Nat. Chem., 2011)

(untitled) - Tasdelen, M. A.; Yagci, Y. (Angew. Chem., Int. Ed., 2013)

(untitled) - Doran, S.; Murtezi, E.; Barlas, F. B.; Timur, S.; Yagci, Y. (Macromolecules, 2014)

(untitled) - Lan, Y.; Lu, Y.; Ren, Z. (Nano Energy, 2013)

(untitled) - Sangermano, M.; Rodriguez, D.; Gonzalez, M. C.; Laurenti, E.; Yagci, Y. (Macromol. Rapid Commun., 2018)

(untitled) - Franchi, D.; Amara, Z. (ACS Sustainable Chem. Eng., 2020)

(untitled) - Yanalak, G.; Doganay, F.; Eroglu, Z.; Kucukkececi, H.; Aslan, E.; Ozmen, M.; Bas, S. Z.; Metin, O.; Hatay Patir, I. (Appl. Surf. Sci., 2021)

(untitled) - Dadashi-Silab, S.; Bildirir, H.; Dawson, R.; Thomas, A.; Yagci, Y. (Macromolecules, 2014)

(untitled) - Kiskan, B.; Zhang, J.; Wang, X.; Antonietti, M.; Yagci, Y. (ACS Macro Lett., 2012)

(untitled) - Kaya, K.; Kiskan, B.; Kumru, B.; Schmidt, B. V. K. J.; Yagci, Y. (Eur. Polym. J., 2020)

(untitled) - Dadashi-Silab, S.; Tasdelen, M. A.; Kiskan, B.; Wang, X.; Antonietti, M.; Yagci, Y. (Macromol. Chem. Phys., 2014)

(untitled) - Dadashi-Silab, S.; Atilla Tasdelen, M.; Mohamed Asiri, A.; Bahadar Khan, S.; Yagci, Y. (Macromol. Rapid Commun., 2014)

(untitled) - Gao, T.; Su, X.; Xu, H.; Hu, H.; Zeng, C.; Gao, Y. (ChemistrySelect, 2020)

(untitled) - Samuel, A. G.; Nagarajan, K.; Cidhuraj, K.; Gopal, B.; Chakravarty, S.; Selvaraj, V.; Lourdusamy, E.; Bhagavathsingh, J. (Appl. Organomet. Chem., 2020)

(untitled) - Dadashi-Silab, S.; Kiskan, B.; Antonietti, M.; Yagci, Y. (RSC Adv., 2014)

(untitled) - Shen, Z.-Y.; Li, L.-Y.; Li, Y.; Wang, C.-C. (J. Colloid Interface Sci., 2011)

(untitled) - Colucci, G.; Mana, S.; Conzatti, L.; Sangermano, M. (Surf. Coat. Technol., 2012)

(untitled) - Mokbel, H.; Graff, B.; Dumur, F.; Lalevée, J. (Macromol. Rapid Commun., 2020)

(untitled) - Dietlin, C.; Schweizer, S.; Xiao, P.; Zhang, J.; Morlet-Savary, F.; Graff, B.; Fouassier, J.-P.; Lalevée, J. (Polym. Chem., 2015)

(untitled) - Li, Z.; Zou, X.; Shi, F.; Liu, R.; Yagci, Y. (Nat. Commun., 2019)

(untitled) - Kocaarslan, A.; Tabanli, S.; Eryurek, G.; Yagci, Y. (Angew. Chem., Int. Ed., 2017)

(untitled) - Suerkan, A.; Alkan, E. A.; Kaya, K.; Udum, Y. A.; Toppare, L.; Yagci, Y. (Prog. Org. Coat., 2021)

(untitled) - Kütahya, C.; Zhai, Y.; Li, S.; Liu, S.; Li, J.; Strehmel, V.; Chen, Z.; Strehmel, B. (Angew. Chem., Int. Ed., 2021)

(untitled) - Zhu, M.; Osakada, Y.; Kim, S.; Fujitsuka, M.; Majima, T. (Appl. Catal., B, 2017)

(untitled) - Ling, X.; Wang, H.; Huang, S.; Xia, F.; Dresselhaus, M. S. (Proc. Natl. Acad. Sci. U. S. A., 2015)

(untitled) - Han, C.; Li, Y.-H.; Li, J.-Y.; Qi, M.-Y.; Tang, Z.-R.; Xu, Y.-J. (Angew. Chem., 2021)

(untitled) - Li, Y.; Wang, H.; Zhang, X.; Wang, S.; Jin, S.; Xu, X.; Liu, W.; Zhao, Z.; Xie, Y. (Angew. Chem., Int. Ed., 2021)

(untitled) - Kalay, E.; Küçükkeçeci, H.; Kilic, H.; Metin, Ö. (Chem. Commun., 2020)

(untitled) - Eken Korkut, S.; Küçükkeçeci, H.; Metin, Ö. (ACS Appl. Mater. Interfaces, 2020)

(untitled) - Kocaarslan, A.; Eroglu, Z.; Yilmaz, G.; Metin, O.; Yagci, Y. (ACS Macro Lett., 2021)

(untitled) - Kütahya, C.; Yagci, Y.; Strehmel, B. (ChemPhotoChem, 2019)

(untitled) - Tiouitchi, G.; Ali, M. A.; Benyoussef, A.; Hamedoun, M.; Lachgar, A.; Benaissa, M.; Kara, A.; Ennaoui, A.; Mahmoud, A.; Boschini, F.; Oughaddou, H.; El Kenz, A.; et al. (Mater. Lett., 2019)

(untitled) - Zhao, M.; Qian, H.; Niu, X.; Wang, W.; Guan, L.; Sha, J.; Wang, Y. (Cryst. Growth Des., 2016)

(untitled) - Wilkening, I.; del Signore, G.; Hackenberger, C. P. R. (Chem. Commun., 2011)

(untitled) - Borissov, A.; Lim, J. Y. C.; Brown, A.; Christensen, K. E.; Thompson, A. L.; Smith, M. D.; Beer, P. D. (Chem. Commun., 2017)

(untitled) - Gong, T.; Adzima, B. J.; Baker, N. H.; Bowman, C. N. (Adv. Mater. (Weinheim, Ger.), 2013)

(untitled) - Baranek, A.; Song, H. B.; McBride, M.; Finnegan, P.; Bowman, C. N. (Macromolecules, 2016)

(untitled) - Arslan, M.; Yilmaz, G.; Yagci, Y. (Polym. Chem., 2015)

(untitled) - Hoogenboom, R.; Moore, B. C.; Schubert, U. S. (Chem. Commun., 2006)